2019
DOI: 10.11604/pamj.2019.33.215.19289
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle accident is a risk factor for traumatic head injury among children in Abuja: analysis of the first trauma registry in Nigeria

Abstract: IntroductionPediatric traumatic injury is a major public health concern that is poorly documented in lower and middle-income countries. This study analyzed data on pediatric injuries from a unique hospital trauma registry in Abuja, Nigeria.MethodsData were analyzed on 220 traumatically injured patients aged 21 years/less to describe injury characteristics and to determine the association between mechanism of injury and pediatric head injuries in Abuja, Nigeria, between 2014 and 2015. Bivariate analysis using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Data from the US Centers for Disease Control and Prevention show that between 2007 and 2013, the number of emergency department visits for traumatic head injury increased in the 0–4 years and 5–14 years age groups, with a 37.8 % increase in the youngest age group[ 40 ]. Research has shown that road traffic accidents are the most common cause of traumatic brain injury in China.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the US Centers for Disease Control and Prevention show that between 2007 and 2013, the number of emergency department visits for traumatic head injury increased in the 0–4 years and 5–14 years age groups, with a 37.8 % increase in the youngest age group[ 40 ]. Research has shown that road traffic accidents are the most common cause of traumatic brain injury in China.…”
Section: Discussionmentioning
confidence: 99%
“…China's new tra c regulations now require the use of child safety seats for children under 4 years of age, and children under 12 years of age cannot ride on the passenger side. Furthermore, with the increase use of vehicles, it is necessary to strengthen the implementation of road safety strategies, such as installing speed bumps, improving emergency medical care for tra c accidents, and enhancing road safety enforcement [31]. In addition, we recommend installing special child safety seats in private cars and even in public transport, in order to reduce child mortality and protect children from more serious high-energy severe trauma in the event of tra c accidents.…”
Section: Changes In the Epidemiology Of Fractures And Etiology In Termentioning
confidence: 99%
“…However, few studies have considered both the built environment and socioeconomic factors when modelling children's and adolescents' involvement in traffic accidents from a spatial perspective [54]. Previous studies have used a variety of statistical methods, such as regression [55] and MC and CA models, to predict pedestrian accidents separately [47,49,50]. In some recent studies, new techniques such as data-driven microscopic design analysis [56], computer vision techniques, neural network analysis and image segmentation mapping approaches [57] have been used to analyse the risk of pedestrian accidents in cities.…”
Section: Introductionmentioning
confidence: 99%